Audience Reception on Future Anxiety Phenomenon in “Masalah Masa Depan” Music Video by Hindia - Ferry Shandy Welianto Wong; Ido Prijana Hadi; Agusly Irawan Aritonang (Journal of Content and Engagement, 2024)
Future anxiety is a condition where individuals experience uncertainty, fear, anxiety, and concern about potential undesirable changes in the future. The varied backgrounds of the informants add appeal to this study. This research aims to understand how the audience interprets the phenomenon of future anxiety in the music video "Masalah Masa Depan." The music video was chosen for its stronger message delivery compared to just the song. This study employs a qualitative method with Stuart Hall's reception analysis approach, categorising informants into three positions: dominant, negotiated, and oppositional. The findings reveal that three informants have dominant reception, three have negotiated reception, and two have oppositional reception. Informants, aged 16-24 and working as final-year students or young employees, perceive future anxiety as a phenomenon influenced by economic and employment factors.